Pengembangan Ekonomi Melalui Pembangunan Manajemen Zakat - Harisah; Zulaekah; R. Suhaimi (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2021)
In the management of zakat which is described by Islam, it can be read in the management built by Rasulullah SAW, the Apostle has delegated the task by appointing amil zakat. The appointment of amil provides an understanding that zakat is not managed by individuals, but is managed professionally and organized. Amil who has responsibility for his duties, collects, stores, and distributes zakat assets to those who are entitled to receive them. Thus, this paper is examined using a qualitative literature method to find zakat management that has an impact on economic development. This study found that the quality of management of a zakat management organization must be measurable. For that, three keywords can be used as a measuring tool. First, trust. Second, professional attitude. Third, transparent.